Prevalence of Work-Related Musculoskeletal Disorders in Factory Workers in Textile Industry Faisalabad - Ramzan, Nadia; Aleem, Fatima; Fatima-Tuz-Zahra; Ali, Mansoor; Khalid, Ayyaz-Bin- (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the prevalence of work-related musculoskeletal disorders and assess the risk factors for work-related musculoskeletal disorders among textile factory workers.Study Design: Cross-sectional study.Place and Duration of Study: Textile factory in the industrial zone of Faisalabad, Pakistan from Jan to Apr 2024.Methodology: A Modified form of Standardized Nordic Musculoskeletal Questionnaire was used to collect data from 300 factory workers, using convenience sampling. Working hours, gender, increasing age and increased sweating, working years, break time, were divided into groups for analysis. Chi square test was applied to determine association between these variables and musculoskeletal disorders.Results: Out of 300 factory workers, the maximum fatigue caused by nature of work was found in 21(7%) on upper limb, three (1%) on lower limb and 276(92%) on both limbs. Forceful exertion was a work- related risk factor in 298(99.3%) respondents while high task repetition was a risk factor in two (0.7%). Working years (p-value=0.007), break time (p-value=0.001), sweating (p-value=0.0025) and age (p-value=0.001) had statistically significant association with work related musculoskeletal disorder. Total 274(91.3%) had no musculoskeletal disorder while 26(8.6%) respondents had musculoskeletal disorder.Conclusions: Prevalence of musculoskeletal disorders in textile sector was less and significant association was found between working years, break time, sweating and presence of Musculoskeletal disorders.